(untitled) (Romano-arabica, 2025)
Code Switching is a communication strategy between individuals and groups; it’s the alternation between two languages whiting the same discourse. The phenomenon is common in language centers for teaching foreign languages. So, we will work through this research to address some of the issues associated with the phenomenon from a social, linguistic and educational perspective. The problem that the research will discuss is, "Is the code switching a building block or a stumbling block to teaching Arabic to non- native speakers? One of the objectives of this research is to demonstrate the importance of code switching and its effectiveness in developing Arabic language teaching and determining its added value. In view of the specific nature of the subject, we have undertaken a field study using the quantitative social approach during the collection of data, through the preparation of two electronic questionnaires for non-speaking Arabic students and their teachers to study the extent of its contribution to the development of linguistic learner’s levels. We concluded that the code switching played an active role in the teaching of Arabic and that there’s nothing abnormal or linguistically disturbing about switching from one language to another in the classroom. It is not an obstacle to a learning process, but only if such use is regulated and made an auxiliary strategy for teaching and learning Arabic.